Booms, recessions and financial turmoil : a fresh look at investment decisions under cyclical uncertainty - Yu-Fu Chen; Michael Funke (Center for Economic Studies and ifo Institute (CESifo), 2009)
The paper studies the interaction between cyclical uncertainty and investment in a stochastic real option framework where demand shifts stochastically between three different states, each with different rates of drift and volatility. In our setting the shifts are governed by a three-state Markov switching model with constant transition probabilities. The magnitude of the link between cyclical uncertainty and investment is quantified using simulations of the model. The chief implication of the model is that recessions and financial turmoil are important catalysts for waiting. In other words, our model shows that macroeconomic risk acts as an important deterrent to investments.
Keywords: D81; D92; E32; 330; business cycles; real options; investment; Markov switching; Tobin's q; uncertainty; Investition; Entscheidung bei Unsicherheit; Realoption; Tobin's Q; Konjunktur; Finanzmarktkrise; Markovscher Prozess; Theorie